Lawyer Dissatisfaction, Emotional Intelligence and Clinical Legal Education - Colin James (Legal Education Review)
This paper reflects on a trial of blended learning conducted in the elective Unit Intellectual Property at the University of Western Sydney over Summer 2008. The trial was conducted in order to establish whether a ‘replacement’ model of blended learning was suitable for law students and to assess the benefits and challenges this model presents. The overall results of the trial demonstrate that, with sufficient time invested in the design and production of quality learning materials, blended learning can potentially deliver significant benefits in this discipline, both to students and also to academics. In particular, the blended mode of delivery offers opportunities to make learning in law units more active, without entirely sacrificing the detailed explanations of content, typical of traditional lectures, that law students often place great value upon. By combining the best aspects of face-to-face and online teaching, this model can offer students the best of both worlds.